Risk and Regulation at the Interface of Medicine and the Arts : Dangerous Currents. - Bleakley, Alan (Alan Douglas); Lynch, Larry, 1975-; Whelan, Gregg
This book brings together an edited selection of presentations from the Association for Medical Humanities annual conference 2015, held at Dartington Hall, UK, that address the question: How might innovative performing arts help to develop medical education and practice? It includes papers and accounts of both keynote talks and performances, presenting cutting-edge activity, thinking and research in the medical and health humanities. The volume also offers an archive of a visual arts exhibition focused on surgical themes that ran in conjunction with the conference. An introductory chapter situa.